Assessment of Staphylococcus aureus along milk value chain and its public health importance in Sebeta, central Oromia, Ethiopia - Ayele, Yodit (BMC Microbiol, 2017)
BACKGROUND: Staphylococcus aureus is one of the leading causes of gastroenteritis acquired from contaminated foods such as milk and milk products. However, such information is limited in Ethiopia. A cross-sectional study was conducted to assess the contamination of milk with S. aureus and knowledge, attitudes and practices (KAP) of actors along the milk value chain in Sebeta, Central Oromia, Ethiopia. A total of 291 samples collected from dairy farms, milk collection centers (MCCs) and processing plant were examined using standard microbiological techniques. The antimicrobial susceptibility profiles of the isolates were also investigated. The KAP of actors in milk value chain were evaluated through a structured questionnaire. RESULTS: Overall, 23.4% (n = 68) of the samples were positive for S. aureus. The prevalence of S. aureus was 19.6% (95% CI: 14.5–25.6) and 80.0% (95% CI: 14.5–25.6) at farm level and MCCs, respectively. Higher isolation rate was observed in the MCCs (p = 0.000) than the farms. The contamination rates of hands of milkers’ and milking buckets with S. aureus were 32% and 11.1%, respectively. S. aureus was not isolated from pasteurized milk samples. The isolates were found to be resistant to cefoxitin (100%), penicillin G (98.5%), and streptomycin (77.9%). Among 23 interviewed farmers, 35% of them consumed raw milk, none of them wash their hands and 82.6% did not wash udder and teat before milking. Six percent of consumers had the habit of raw milk consumption. Eighty seven percent of dairy farmers and 54% of consumers had no awareness about milk borne diseases and staphylococcal food poisoning. CONCLUSIONS: The study revealed a high prevalence of S. aureus along the milk value chain, poor milk handling practices, raw milk consumption behavior, lack of awareness about milk borne diseases and occurrence of antimicrobials resistant S. aureus. S. aureus seems to pose a public health risk in Sebeta. Authors recommended the urgent need of public awareness creation about the importance of hygienic milk production and proper handling and adequate heat treatment of milk before consumption and further study to assess cost-effective preventive and control options.